2016
DOI: 10.1186/s13195-016-0211-0
|View full text |Cite
|
Sign up to set email alerts
|

Identifying biomarkers of dementia prevalent among amnestic mild cognitively impaired ethnic female patients

Abstract: BackgroundThere is a need to investigate biomarkers that are indicative of the progression of dementia in ethnic patient populations. The disparity of information in these populations has been the focus of many clinical and academic centers, including ours, to contribute to a higher success rate in clinical trials. In this study, we have investigated plasma biomarkers in amnestic mild cognitively impaired (aMCI) female patient cohorts in the context of ethnicity and cognitive status.MethodA panel of 12 biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Studies by Craig-Schapiro et al [45], Choi et al [124], and Grewal et al [93] have given hope for its use in diagnostics of early stage dementias (MCI and mild stage AD). Less promising results were acquired by Villar-Pique et al [126].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Craig-Schapiro et al [45], Choi et al [124], and Grewal et al [93] have given hope for its use in diagnostics of early stage dementias (MCI and mild stage AD). Less promising results were acquired by Villar-Pique et al [126].…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant concentration differences of YKL-40 among subgroups were identified only in the Latin American group. In addition, other measured biomarkers showed the differences of sensitivity among ethnic groups [93]. Amnestic type MCI is a state highly predisposing to AD, contrary to non-amnestic types which are the bases for developing other dementias.…”
mentioning
confidence: 97%
“…A few studies have evaluated in an AA cohort the use of plasma proteins or metabolites as a fluid biomarker for AD, but none of these have evaluated plasma cf-mRNAs. 9 , 39 , 40 , 41 , 42 , 43 Future studies should systematically evaluate the biomarker potential of all transcripts detectable in plasma in diverse populations and incorporate these plasma cf-RNAs into a biomarker panel along with plasma levels of proteins and metabolites that have been shown to effectively discriminate AD from CU and other types of dementias, such as Aß42/Aß40 ratio and p-tau, in order to achieve greater discriminatory potential and add theragnostic value.…”
Section: Discussionmentioning
confidence: 99%
“…A Washington Heights and Inwood Community Aging project community-based study of plasma biomarkers found no significant differences across Hispanic, Black, and NHWs in concentrations of t tau, Aβ 40 , Aβ 42 , or NfL ( 24 ). Gerwal et al ( 25 ) in a small study of women ( N = 15 in each group) with MCI reported higher levels of Aβ 40 and Aβ 42 in Hispanic women compared to AA and NHW women. A study of plasma biomarkers in AAs including tau and Aβ 42 comparing cognitively unimpaired individuals with Alzheimer's patients found that tau was significantly higher in the AD group and Aβ 42 level was not associated with Alzheimer's ( 26 ).…”
Section: Introductionmentioning
confidence: 96%